O papel das agências de rating: evidências da crise asiática - Palazzi, Rafael Baptista (2011)
The actual study aims to analyze the role of credit rating agencies in the world crisis, focusing on the Asian crisis, the Agencies whose work had an important role. We have argued that in Asian crisis the rating agencies have not been able to anticipate the crisis and have acted in a way to intensify it. This paper presents, previously, the historical background of the Rating Agencies and analyzes the structure of the methodology disclosed by them, which is used for classification of the ratings. Through the relevant literature review it will be analyzed the determinants and impacts of the ratings in emerging market economies, particularly in the Asian crisis. Therefore it will be discussed the role of the rating Agencies in the Asian crisis and, briefly, it will be shown the acting of rating agencies in the other world crises